Performance of Goats Fed Moringa oleifera Leaf Meal Incorporated in Concentrate Mixture - Ali, Syed Bilal; Kawitkar, S.B.; Deshmukh, A.D.; Dhok, A.P.; Jawale, M.R.; Chopde, S.V.; Parihar, N.B. (Indian Journal of Animal Nutrition, 2018)
An experiment was conducted to assess the growth performance of goats fed Moringa oleifera leaf meal incorporated in concentrate mixture for 90 days. Twelve goats were divided into 2 groups of 6 animals each. The animals in group T0 (control) received a concentrate mixture containing cotton seed cake (CSC) along with ad lib. fodder whereas in group T1, 50% of CSC proportion in concentrate mixture was replaced by M. oleifera leaf meal. The values for average DM intake, feed conversion ratio and digestibility of nutrients (DM, CP, EE and CF) were similar in two groups whereas NFE digestibility was significantly (P<0.05) higher in T1 group. The cost of production per kg gain in group T1 was ` 173.67 compared to `195.87 in control group. Therefore, M. oleifera leaf meal could safely replace cottonseed cake as a protein concentrate source up to 12.5 parts of concentrate mixture for economical rearing of growing goats without any adverse effect on the growth performance.